The Grande and Petite Histoire of Thomas Chapais: Formalizing the Frameworks of Monographs and Synthesis in Early Twentieth‑Century French Canadian Historiography - Chahine, Karim (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2025)
Thomas Chapais (1858–1946) was one of the first French Canadian historians to devote attention, in his written works and speeches, to the forms that history writing can take. At a time when his reputation was already well established, he developed an original way of thinking about historical writing, explicitly adopting a literary and poetic conception of history. Underlying these ideas about form were two approaches to history based on a single mode of inquiry but using different focal points for observation: grande histoire and petite histoire. Prior to this reflection, Chapais attempted to resolve the tension between “impartiality” and “impassivity.” This enabled him to develop his conception of the ideal historian, concerned with historical truth and an attachment to a national reality.